The Effect of Mechanical Agitation Duration on Root Canal Irrigation Techniques (on the cleanliness of dentinal tubules in the middle third of the root canal) - Badi Soerachman; Mutiara Sukma Suntana; Iftinan Alma (Sean Institute, 2025)
This study aimed to evaluate the effectiveness of irrigation solution application time duration in cleaning dentinal tubuli in the middle third of the root canal through Passive Ultrasonic Irrigation (PUI) and manual agitation irrigation techniques. This study was a laboratory experiment with posttest-only control group, involving 16 extracted mandibular premolars and divided into four treatment groups according to the duration of irrigation application (15 and 30 seconds) and the irrigation technique used. Evaluation of detine tubuli clearance was performed by Scanning Electron Microscope (SEM), and statistical analysis was performed by Kruskal-Wallis test. The results showed no significant difference in dentinal tubule clearance between treatment groups (p = 0.120; p > 0.05). Thus, 15 and 30 seconds of irrigation solution application time duration in the mechanical agitation technique had no significant effect on the cleanliness of dentinal tubules in the middle third of the root canal.